Peningkatan Keterampilan Berpikir Kritis IPA Siswa Melalui Model Pembelajaran Berbasis Masalah - Neneng Agustiningsih; Nofita Wabadi Yaningsi; Muhammad Harja Effendi (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2022)
This study aims to improve students' critical thinking skills through the Problem Based Learning model in science subjects VII MTS Nurul Islam Sekarbela, Mataram. This type of research is quasi-experimental with a quantitative approach with a non-equivalent control group design. The population of class VII students are four classes, two female classes, namely VII A and B and two male classes, namely VII C and D, with a total of 120 students. The research sample is class A and B with a cluster random sampling technique by drawing lots to determine the experimental and control classes. Data collection techniques in this study were observation and tests. The test instrument has been tested for the validity of 10 questions, the value of r count (0.383-0.646) > r table (0.381) and reliability of 0.570 with a reliable category. There are two data analysis techniques, namely descriptive, which consists of the analysis of the implementation of learning and critical thinking skills, and differential techniques consisting of normality testing, homogeneity testing and hypothesis testing. Hypothesis testing in this study uses the Anacova test (Analysis of Covariance) with a significance level of = 0.05 with test criteria. If the value of sig < 0.05, then H0 is rejected, whereas if the sig value > 0.05, then H0 is accepted. The data from the hypothesis test results show that H0 is rejected and Ha is accepted. So this study concludes that there is an effect of problem-based learning on students' critical thinking skills in science.